Peran Media Sosial Tiktok dalam Transformasi Politik Gen Z Pada Pemilihan Presiden Tahun 2024 di Kelurahan Tegal Rejo - Alfon Apriel Simanullang; Prayetno (Jurnal Administrasi Politik dan Sosial, 2025)
This study aims to analyze the role of TikTok social media in Gen Z's political transformation during the 2024 presidential election in Tegal Rejo Village. In the context of digital technology development, TikTok has become an influential platform for disseminating political information, especially among the younger generation. This social media not only functions as a means of entertainment, but also as an effective political communication tool for campaigns, policy dissemination, and shaping public opinion. This study uses a qualitative method with a case study approach, involving direct observation and in-depth interviews with residents of Tegal Rejo Village who actively use TikTok. The data obtained will be analyzed to understand how political content on TikTok influences the political awareness, participation, and voting decisions of the village community. The results of this study are expected to provide new insights into the dynamics of political communication in the digital era and the contribution of social media in shaping political mindsets and behavior at the local level